2003
DOI: 10.1088/0031-9155/48/9/309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dextran-induced changes in refractive index and aggregation on optical properties of whole blood

Abstract: The purpose of the present study is to investigate systematically the mechanisms of alterations in the optical properties of whole blood immersed in the biocompatible agent dextran, and to define the optimal concentration of dextrans required for blood optical clearing in order to enhance the capability of light penetration depth for optical imaging applications. In the experiments, dextrans with different molecular weights and various concentrations were employed and investigated by the use of the optical coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 35 publications
3
65
1
1
Order By: Relevance
“…Therefore, BGC can be measured by analyzing the glucoseinduced changes in the OCT signal slope detected from the biological tissues, such as the dermis area of the skin. 38 The skin consists of three major layers: stratum corneum (SC), epidermis, and connective tissue of dermis, which is the only layer containing a developed blood microvessel network. The OCT technique allows measurement of glucoseinduced changes in the skin-scattering coefficient directly from the dermis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, BGC can be measured by analyzing the glucoseinduced changes in the OCT signal slope detected from the biological tissues, such as the dermis area of the skin. 38 The skin consists of three major layers: stratum corneum (SC), epidermis, and connective tissue of dermis, which is the only layer containing a developed blood microvessel network. The OCT technique allows measurement of glucoseinduced changes in the skin-scattering coefficient directly from the dermis.…”
Section: Introductionmentioning
confidence: 99%
“…7 Our previous OCT study demonstrated that dextrans with various molecular weights (MWs) led to optical clearing in stationary blood samples from 52.1% to 150.5%. 8,9 The optical properties of blood are altered by two effects induced by dextrans: refractive index matching and erythrocyte aggregation. [9][10][11] However, the effect of erythrocyte aggregation on optical clearing of blood was not mentioned in Brezinski's work, 7 where only index matching was discussed for circulation of blood in a high flow rate using only one dextran with MW 70 kDa.…”
Section: Introductionmentioning
confidence: 99%
“…Scattering properties are dependent on the refractive index of the scatterers as well as that of the base medium (extracellular medium or blood plasma) which affect blood osmolarity [1]. Scattering and light propagation are also affected by the size and shape of RBCs and their aggregation properties [1]- [5]. Optical clearing is a promising technique to decrease light scattering in a biological tissue [6].…”
mentioning
confidence: 99%
“…However, optimal concentrations of OCAs serve to reduce the scattering properties of blood [7], which have been studied extensively both experimentally [8]- [10] and theoretically [11], [12]. In addition, several groups are investigating the optical properties of whole blood [1], [13], [14] as well as RBC aggregates at the whole blood level [3]- [5] and in RBC suspensions [15]. This helps the analysis and understanding of optical measurement results.…”
mentioning
confidence: 99%